(untitled) (Asian Journal of Plant Biology, 2014)
Nonlinear regression of a data and its subsequent statistical analysis relies on the facts that the residuals (difference between observed and predicted data) followed a normal or Gaussian distribution, no autocorrelation and are free of outliers. Previously, we demonstrated that the Buchanan- three phase growth kinetics is the best model using the ordinary least squares method for the growth of the algae Chlorella vulgaris compared to other models such as modified logistic, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts, Von Bertalanffy, Huang and the Buchanan three-phase linear model. If all of these assumptions are satisfied, the test is said to be robust. In this work we perform statistical diagnostics to the residuals and discovered the presence of an outlier that allows the residuals to be normally distributed and satisfy other diagnostic tests after its removal.